Revisiting spatial scale in the productivity–species richness relationship: fundamental issues and global change implications - McBride, Paul D.; Cusens, Jarrod; Gillman, Len N. (AoB plants, 2014)
The relationship between climate and biodiversity has been long debated. In a changing environment, there is new emphasis to resolve this debate for practical reasons: to manage conservation efforts we need to understand how diversity will change from both our own actions and natural global cycles. We show that the roles played by different ecological and evolutionary factors in shaping plant diversity change across the world's ecoregions, and—critically—that these differences scale with ecoregion size. Ecoregions that are both large and productive are globally important biodiversity sources that shape the biota of the smaller regions around them. Abstract The relationship between net primary productivity (NPP) and species richness has been the subject of long-running debate. A changing climate gives added impetus to resolving this debate, as it becomes increasingly necessary to predict biodiversity responses that might arise from shifts in productivity or its climatic correlates. It has become increasingly clear that at small scales productivity–species richness relationships (PSRs) are variable, while at macro scales relationships are typically positive. We demonstrate the importance of explicitly considering scale in discussions on PSRs even at large scales by showing that distinct patterns emerge in a global dataset of terrestrial ecoregions when ecoregions are binned into size classes. At all sizes, PSRs in ecoregions are positive, but the strength of the PSR scales positively with ecoregion size. In small ecoregions (103–104 km2), factors correlating with productivity play only a minor role in species richness patterns, while in large ecoregions (>105 km2), NPP modelled from remotely sensed data is able to explain most of the variation in species richness. Better understanding the effects of scale on PSRs contributes to the debate on the relationship between species richness and productivity, which in turn allows us to better predict how both long- and short-term biodiversity patterns and ecosystem functioning might be altered under global change scenarios. This gives focus on future research to clarify causal pathways between species richness and productivity with appropriate attention to scale as an important focusing element.